Construction Methods and Planning. - Illingworth, J. R. (John Rodger) (London : E. & F. N. Spon, 2000)
This text introduces students of construction management to the selection of construction methods, their planning and site organization. It discusses the factors which determine the planning of construction methods and application of these tools.
Keywords: Building -- Planning; Construction industry -- Management; House and Home